Fournier’s Gangrene: Lessons Learned from Multimodal and Multidisciplinary Management of Perineal Necrotizing Fasciitis - Ioannidis, Orestis; Kitsikosta, Loukiani; Tatsis, Dimitris; Skandalos, Ioannis; Cheva, Aggeliki; Gkioti, Aikaterini; Varnalidis, Ioannis; Symeonidis, Savvas; Savvala, Natalia Antigoni; Parpoudi, Styliani; Paraskevas, George K.; Pramateftakis, Manousos George; et al. (Frontiers in Surgery, 2017)
Background Fournier’s gangrene (FG) is a rapidly evolving necrotizing fasciitis of the perineum and the genital area, the scrotum as it most commonly affects man in the vast majority of cases. It is polymicrobial in origin, due to the synergistic action of anaerobes and aerobes and has a very high mortality. There are many predisposing factors including diabetes mellitus, alcoholism, immunosuppression, renal, and hepatic disease. The prognosis of the disease depends on a lot of factors including but not limited to patient age, disease extent, and comorbidities. The purpose of the study is to describe the experience of a general surgery department in the management of FG, to present the multimodal and multidisciplinary treatment of the disease, to identify predictors of mortality, and to make general surgeons familiar with the disease. Methods The current retrospective study is presenting the experience of our general surgery department in the management of FG during the last 20 years. The clinical presentation and demographics of the patients were recorded. Also we recorded the laboratory data, the comorbidities, the etiology, and microbiology and the therapeutic interventions performed, and we calculated the various severity indexes. Patients were divided to survivors and non-survivors, and all the collected data were statistically analyzed to assess mortality factors using univariate and then multivariate analysis. Results In our series, we treated a total of 24 patients with a mean age 58.9 years including 20 males (83.4%) and 4 females (16.6%). In most patients, a delay between disease onset and seeking of medical help was noted. Comorbidities were present in almost all patients (87.5%). All patients were submitted to extensive surgical debridements and received broad-spectrum antibiotics until microbiological culture results were received. Regarding all the collected data, there was no statistically significant difference between survivors and non-survivors except the presence of malignancy in non-survivors (p = 0.036) and the lower hemoglobin (p < 0.001) and hematocrit (p = 0.002) in non-survivors. However, multivariate analysis did not reveal any predictor of mortality. Conclusion Early diagnosis, aggressive thorough surgical treatment, and administration of the proper antibiotic treatment comprise the cornerstone for the outcome of this disease. In small populations like in the present study, it is difficult to recognize any predictors of mortality and even the severity indexes, which take into account a lot of data cannot predict mortality.